Identification by Suppression Subtractive Hybridization of Frankia Genes Induced under Nitrogen-Fixing Conditions - Yamaura, Masatoshi (American Society for Microbiology (ASM), 2010)
Frankia is an actinobacterium that fixes nitrogen under both symbiotic and free-living conditions. We identified genes upregulated in free-living nitrogen-fixing cells by using suppression subtractive hybridization. They included genes with predicted functions related to nitrogen fixation, as well as with unknown function. Their upregulation was a novel finding in Frankia.